Daratumumab monotherapy for relapsed/refractory multiple myeloma, focussed on clinical trial‐unfit patients and subsequent therapy. (27th December 2020) - Park, Sung‐Soo; Min Byun, Ja; Yoon, Sung‐Soo; Kim, Kihyun; Jung, Sung‐Hoon; Lee, Je‐Jung; Min, Chang‐Ki
Summary: Real‐world outcomes of daratumumab monotherapy (DM) for relapsed/refractory multiple myeloma (RRMM) have remained unclear. We conducted a multicentre retrospective study of 107 patients receiving DM for RRMM. The cohort included 64 trial‐unfit patients whose characteristics could not meet inclusion criteria in two previous clinical trials (GEN501 and SIRIUS). The overall response rate (ORR), and median first and second progression‐free survival (PFS1 and PFS2) and overall survival were 42·1%, and 3·6, 8·1 and 11·9 months, respectively. Refractoriness to carfilzomib and/or lenalidomide, and neutropenia (<1.0 × 10 9 /l) resulted in poorer ORRs. An Eastern Cooperative Oncology Group Performance Status of ≥3, neutropenia (<1.0 × 10 9 /l), thrombocytopenia (<75 × 10 9 /l), and renal failure (glomerular filtration rate of <20 ml/min/1·73 m 2 ) were associated with poor PFS1 and PFS2 in respective univariate analysis. The modified trial‐unfit group, based on the above factors, showed significantly negative impacts on PFS1 and PFS2 (hazard ratio 2·823 and 3·677, all P  < 0·001) in multivariate analysis despite having a 34% ORR. Fatal infections occurred more often in the modified trial‐unfit group than in the others (16·1% vs. 4·3%; P  = 0·099). Despite failure of DM, subsequent therapy with pomalidomide‐based therapy or carfilzomib‐dexamethasone provided a 66·6% ORR. Real‐world DM showed favourable efficacies for RRMM and, potentially, additional benefits with subsequent therapies. However, characteristics corresponding with trial‐unfitness might offset the efficacy of DM.